Political Communication Strategy of The Golongan Karya Party in Manggarai Regency for Winning The 2024 Elections in Manggarai Regency, East Nusa Tenggara - Naku, Robertus Kristianto; Zulkarnain, Iskandar; Ridho, Hatta (Journal of Social Interactions and Humanities, 2024)
This research aims to analyze the political communication strategy of the Golongan Karya (Golkar) Party as well as its supporting and inhibiting factors in winning the 2024 General Election in Manggarai Regency, East Nusa Tenggara. Using Harold Laswell's five elements of communication analysis (communicator, message, channel, communicant, and effect) and a qualitative method with a post-positivistic phenomenological approach, this research involved experienced Golkar cadres as well as community leaders who understand political parties. Data were collected through in-depth interviews, focus group discussions, observation, and documentation. The results showed that Golkar's communication strategy includes strict selection of cadres, effective packaging of political messages, utilization of various communication channels, voter segmentation, and evaluation of communication effects. Supporting factors include cadre popularity, political literacy, culture, media, and neutrality of religious institutions. The inhibiting factors include cadre professionalism, money politics, social media, and stigma or labeling.